Bud, not Buddy - Curtis, Christopher Paul; Delacorte Press (New York : Delacorte Press, 1999)
Ten-year-old Bud, a motherless boy living in Flint, Michigan, during the Great Depression, escapes a bad foster home and sets out in search of the man he believes to be his father--the renowned bandleader, H.E. Calloway of Grand Rapids
Mitten Award 1999, Michigan Library Association -- Children's Services Division
950
Middle School
Accelerated Reader
Reading Counts!
AR
Coretta Scott King Award, author, 2000
Keywords: Runaway children -- Michigan -- History -- 20th century -- Juvenile fiction; African Americans -- Michigan -- History -- 1877-1964 -- Juvenile fiction; Depressions -- 1929 -- Juvenile fiction; Runaways -- Fiction; African Americans -- Fiction; Depressions -- 1929 -- Fiction; Depressions -- 1929 -- Juvenile fiction; Children's stories; Newbery Medal award winners; Coretta Scott King Author Award winners; Curriculum resource; Historical fiction; Curriculum resource; Historical fiction; Novels